(untitled) (Nigerian Journal of Technology, 2017)
As Public-Private Partnerships (PPPs) are being practiced in most parts of the world, the need to adopt a system mechanism to evaluate the performance is imperative. The paper evaluates sustainable key performance indicators (KPIs) with a view to appreciating times of improved performance or otherwise. Eleven performance indicators for PPP in Nigeria were identified and ranked on a scale of 1 to 5 as follows: It indicates that increased road network size with mean score of 4.65 is the highest rated key performance indicator in a PPP project. Other important factors include Increased asset value, Increased road usage, Reduced road accident, Reduced travel time, Reduced user cost, Reduced maintenance cost, Reduced public sector administration costs, with mean scores of 4.14, 3.99, 3.75, 3.65, 3.59, 3.53, 3.39 respectively. The research alternative hypothesis is "Increased road network size is the most accepted performance indicator for evaluating progress of PPP financed projects". Chi-Square was adapted to test the hypothesis and it rejected the null hypothesis and accepted the alternative hypothesis. It follows that increased road network size is the most rated performance indicator in evaluating PPP projects. Good service outcome is the target of any PPP project and its achievement attaches value for money (VFM) and general confident to the project. http://dx.doi.org/10.4314/njt.v36i4.9